RF energy harvesting prototype operating on multiple frequency bands with advanced power management - Diagarajan M.S.; Ramasamy A.; Boopalan N.; Din N.Bt.Md. (Institute of Advanced Engineering and Science, 2023)
Radio Frequency (RF) harvesting seems to be catching up as an alternate energy source whereby RF energy is scavenged from ambient sources and converted into renewable energy in terms of DC power. This converted DC power is then utilized to power up devices that require a low start up power in which eliminates the need for battery replacement. In this paper, a novel RF energy harvesting prototype is presented which consists of two microstrip patch antennas operating on GSM (900MHz) and WIFI (2.4GHz) & WiMAX (2.3GHz) frequency bands with a bandwidth of 220MHz and 10.11MHz respectively to harvest RF signals from ambience. Two matching networks are presented as well to ensure efficient power transfer to load. Rectifiers are designed to transform the RF signals to DC power. The converted DC signals are then combined and fed to a power management circuit which charges a 4.2V NiMh battery and drives a load at a regulated output of 3V. Copyright 2020 Institute of Advanced Engineering and Science. All rights reserved.